A Systematic Review of the Treatment of Fears and Phobias Among Children with Autism Spectrum Disorders - LYDON, SINEAD; HEALY, OLIVE (Springer, 2014)
Research indicates that fears and phobias are significantly more prevalent, and emerge in response to a greater variety of stimuli, among children with autism spectrum disorders (ASD) than among their developmentally disabled or typically developing peers. Such findings are problematic given the difficulty of assessing and identifying fears or phobias among the ASD population and the challenge of identifying effective treatments for those with core diagnostic deficits in comprehension, communication, and attentional skills. The current review aimed to evaluate the literature describing interventions to treat fears, specific phobia, or social phobia among children with ASD and to identify evidence-based practice in this area. The review indicated that a variety of interventions, described as both traditional and novel, were successful in treating fearful or phobic behavioral responses to stimuli. The findings also suggest that behavioral intervention, including reinforcement, modeling, and exposure, may be considered evidence-based practice in the treatment of fears and phobias among children with ASD. However, the current research base is limited by the predominant focus on the behavioral element of the fear response, and the lack of research examining the cognitive or physiological responses during assessment or treatment.
PUBLISHED
Keywords: treatment; intervention; asperger; autism; ASD; phobia; Fear